Pengaruh Sikap, Norma Subjektif, Dan Kontrol Perilaku Terhadap Kepatuhan Wajib Pajak - Rosalia, Rosalia; Arifin, Arifin (Jurnal Portofolio : Jurnal Manajemen dan Bisnis, 2026)
This study aims to analyze the influence of attitude, subjective norms, and perceived behavioral control on taxpayer compliance. The theoretical foundation of this study is the Theory of Planned Behavior, which emphasizes the role of psychological factors in shaping individual behavior. This research adopts a quantitative approach using a survey method targeting individual taxpayers. Data were collected through questionnaire distribution and analyzed using regression analysis and structural model testing. The results indicate that attitude and subjective norms do not have a significant effect on taxpayer compliance. In contrast, perceived behavioral control has a positive and significant influence on taxpayer compliance. These findings suggest that individuals’ ability to understand, manage, and fulfill their tax obligations is the primary factor driving compliance. This study implies that efforts to improve tax compliance should focus on enhancing taxpayers’ ease, understanding, and capability in meeting their tax obligations.